PENINGKATAN PRESTASI BELAJAR BIDANG STUDI BAHASA INDONESIA MATERI FANTASI DENGAN METODE SNOWBALL THROWING - Kustyarini, Kustyarini; Asiyah, Siti (Jurnal Likhitaprajna, 2019)
The learning process will always be missed by the students if the implementation is done by means of interesting learning styles with the term paikem which is processed in various directions, raises many ideas, is encouraging, expresses, moves the behavior of individuals to play an active role and is able to manage the learning process that is commanded, managed, manipulated, creativity and independence that are in accordance with individual abilities at certain stages. Research on this occasion was patterned with a type of classroom action research consisting of three cycles. Each cycle consists of four stages, namely: design, activity, observation, reflection, and revision. The subject of this research is the first semester students of Class VIl SMP Islam Nurul Huda Poncokusumo Malang Academic Year 2018/2019. Data obtained in the form of formative test results, observation sheets of teaching and learning activities. The model used is Snowball Throwing with the following stages. (1) The teacher delivers the material to be presented; (2) Next, form groups and call each group leader to give an explanation of the material, each group leader returns to his group, followed by explaining the material conveyed by the teacher to his friend; (3) Each student is given one sheet of paper, to write down any questions related to the material explained by the group leader. Obtained the results of data analysis, that student learning achievement has increased from cycle I to cycle III. When the first cycle (66.67%), then the second cycle (76.19%), and the last cycle III (93.48%). The present study concluded that learning with the Snowball Throwing method can have a positive effect on the learning achievement and motivation of first semester students of Class VII SMP Islam Nurul Huda Poncokusumo Academic Year 2018/2019, also this learning model can be used as one of the Indonesian learning alternatives. increase student learning motivation.Â  Keywords: classroom action research, fantasy material, snowball throwing method